Potential causal effect of posttraumatic stress disorder on alcohol use disorder and alcohol consumption in individuals of European descent: A Mendelian Randomization Study. (24th June 2021) - Bountress, Kaitlin E.; Wendt, Frank; Bustamante, Daniel; Agrawal, Arpana; Webb, Bradley; Gillespie, Nathan; Edenberg, Howard; Sheerin, Christina; Johnson, Emma; ,; Polimanti, Renato; Amstadter, Ananda
Abstract: Background: Posttraumatic stress disorder (PTSD) often co‐occurs with alcohol consumption (AC) and alcohol use disorder (AUD). However, it is unknown whether the same etiologic influences that underlie PTSD co‐occurring with AUD are those that underlie PTSD and AC individually. Methods: This study used large‐scale genome‐wide association study (GWAS) data to test whether PTSD and drinks per week [DPW]/AUD are causally related to one another, and, if so, whether PTSD precedes DPW/AUD and/or vice versa. We used Mendelian Randomization methods to analyze European ancestry GWAS summary statistics from the Psychiatric Genomics Consortium (PGC; PTSD), GWAS & Sequencing Consortium of Alcohol and Nicotine Use (GSCAN; DPW), and the Million Veteran Program (MVP; AUD). Results: PTSD exerted a potentially causal effect on AUD ( β  = 0.039, SE = 0.014, p  = 0.005), but not on DPW ( β  = 0.002, SE = 0.003, p  = 0.414). Additionally, neither DPW ( β  = 0.019, SE = 0.041, p  = 0.637) nor AUD ( β  = 8.87 × 10 −4, SE = 0.001, p  = 0.441) exerted a causal effect on PTSD. Conclusions: These findings are consistent with the self‐medication model, in which individuals misuse alcohol to cope with aversive trauma‐related symptoms. These findings extend latent analysis and molecular findings of shared and correlated risk between PTSD and alcohol phenotypes. Given the health behaviors associated with these phenotypes, these findings are important in that they suggest groups to prioritize for prevention efforts. Further, they provide a rationale for future preclinical and clinical studies examining the biological mechanisms by which PTSD may impact AUD. Abstract : Posttraumatic Stress Disorder (PTSD) often co‐occurs with increased alcohol consumption (AC) and alcohol use disorder (AUD). However, it is unknown whether the same influences underlying PTSD‐AUD underlie PTSD‐AC. This study used genome‐wide data from those of European ancestry to investigate whether PTSD, AUD and AC are causally related. Results indicate that PTSD is causally related to AUD; no other causal relations were found. Findings are consistent with the self‐medication model, in which individuals misuse alcohol to cope with trauma‐related symptoms.